A Diels-Alder polymer platform for thermally enhanced drug release toward efficient local cancer chemotherapy. Issue 1 (31st December 2021) - Fujisawa, Nanami; Takanohashi, Masato; Chen, Lili; Uto, Koichiro; Matsumoto, Yoshitaka; Takeuchi, Masayuki; Ebara, Mitsuhiro
ABSTRACT: We reports a novel thermally enhanced drug release system synthesized via a dynamic Diels-Alder (DA) reaction to develop chemotherapy for pancreatic cancer. The anticancer prodrug was designed by tethering gemcitabine (GEM) to poly(furfuryl methacrylate) (PFMA) via N -(3-maleimidopropionyloxy)succinimide as a linker by DA reaction (PFMA-L-GEM). The conversion rate of the DA reaction was found to be approximately 60% at room temperature for 120 h. The reversible deconstruction of the DA covalent bond in retro Diels-Alder (rDA) reaction was confirmed by proton nuclear magnetic resonance, and the reaction was significantly accelerated at 90 °C. A PFMA-LGEM film containing magnetic nanoparticles (MNPs) was prepared for thermally enhanced release of the drug via the rDA reaction. Drug release was initiated by heating MNPs by alternating magnetic field. This enables local heating within the film above the rDA reaction temperature while maintaining a constant surrounding medium temperature. The MNPs/PFMA-L-GEM film decreased the viability of pancreatic cancer cells by 49% over 24 h. Our results suggest that DA/rDA-based thermally enhanced drug release systems can serve as a local drug release platform and deliver the target drug within locally heated tissue, thereby improving the therapeutic efficiency and overcoming the side effects of conventional drugs used to treat pancreatic cancer. Graphical abstract: uf0001